Methods design concept an effective approach for profitability. - Sakamoto, Dr. Shigeyasu
A company achieved 1000 percent increase in profitability with an improvement of around 500 percent in productivity. One of the factors that lead to the success is the changes made in their approach of methods improvement. That is designing new working methods on white papers rather than analysis of present methods with industrial engineers. I believe, real new and effective methods can not be obtained without new approach of designing such as MDC. Profitability oriented management of productivity is also an important matter. Profitability has been declining year by year as well as growth in sales and market shares of Japanese manufacturers. It is not unusual that productivity activities do not directly contribute to corporate performance because of if the productivity improvement is mainly depend on capital investment or autonomy activities. MDC has achieved high level of productivity improvement such as reductions in actual headcounts according to the number of workers rather than reducing required man-hours or shorterning cycle times through work simplification, KAIZEN approach.
Keywords: ROI : return on investment; Productivity; Changing approach; ULC; Unit labor cost; Profitability; MDC : methods design concept; BF : basic functions; AF : auxiliary functions; Kaizenshiro : the design targets are set as; ICT :: ideal cycle time; Empty gain, it is does not stand out in business results